Easy Microsoft Windows 7 : See It Done : Do It Yourself - Soper, Mark Edward (Indiana QUE)
The easiest, friendliest, most visual guide to Windows 7. Microsoft's newest, most powerful version of Windows! For every novice Windows 7 user - including millions who are upgrading from older versions of Windows. The perfect step-by-step, full-colour visual complement to Windows 7's revamped desktop, features, accessories and interface. Thoroughly revamped for Windows 7's latest capabilities - including optional downloadable Windows Live Essential features many Windows 7 books will ignorSummaryThis year, millions of beginner-to-intermediate-level PC users will be searchingfor the easiest possible way to master Windows 7's new features - and withEasy Microsoft Windows 7, they'll find exactly what they're looking for. This full colour, simple, step-by-step book has been carefully crafted to provide instant access to the tasks they need to master. As with all books in the Easy series, it is designed to teach visually: readers never have to work their way through lengthy text explanation.
Include Illustration, Glossary and Index
Keywords: Operating systems (Computers) -- Microsoft Windows (Computer file)